In search of survival strategies – Milka Žicina’s socialist-forced-labor-camp prose (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
The literary output of Milka Žicina (1902–1984) had been underestimated by literary scholars for many years, and its interpretation had been limited almost exclusively to the two interwar novels (Kajin put 1934, Devojka za sve 1940), analyzed within the narrow confines of social literature. The chance to reinterpret her output appeared with the publication of the author’s socialist prison forced-labor prose, which is one of artistically outstanding testimonies of the Cominform period. The primary objectives of the article are (1) the analysis of two texts from Žicina’s socialist prison forced-labor prose – Sve, sve, sve... (2002) and Sama (2009), representing the author’s attempts to deal with the difficulties she faced after leaving the forced-labor prison, and (2) the presentation of the strategies – which emerge from the texts – used by the author to cope with the burden of her own experiences both at the time of her isolation and after the end of the punishment.
Keywords: Cominform; exclusion; stigmatization; socialist prison forced-labor prose